2019
DOI: 10.3389/fonc.2019.01182
|View full text |Cite|
|
Sign up to set email alerts
|

Oncolytic Adenovirus—A Nova for Gene-Targeted Oncolytic Viral Therapy in HCC

Abstract: Hepatocellular carcinoma (HCC) is one of the most frequent cancers worldwide, particularly in China. Despite the development of HCC treatment strategies, the survival rate remains unpleasant. Gene-targeted oncolytic viral therapy (GTOVT) is an emerging treatment modality—a kind of cancer-targeted therapy—which creates viral vectors armed with anti-cancer genes. The adenovirus is a promising agent for GAOVT due to its many advantages. In spite of the oncolytic adenovirus itself, the host immune response is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 104 publications
(112 reference statements)
0
31
0
Order By: Relevance
“…Different species of Ads have various receptors to infect the target cell. Coxsackievirus-Ad receptor (CAR) is known as the main receptor of Ads, while CD46, CD80, CD86, and desmoglein-2 (DSG2) are other receptors for Ads [ 43 ]. Ads require two interactions to infect target cells: (1) binding the fiber knob of the virus to the cell surface receptor and (2) binding the arginine-glycine-aspartic acid (RGD) motif in the penton base of Ads to target cells integrin, specifically αvß3 [ 44 ].…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
“…Different species of Ads have various receptors to infect the target cell. Coxsackievirus-Ad receptor (CAR) is known as the main receptor of Ads, while CD46, CD80, CD86, and desmoglein-2 (DSG2) are other receptors for Ads [ 43 ]. Ads require two interactions to infect target cells: (1) binding the fiber knob of the virus to the cell surface receptor and (2) binding the arginine-glycine-aspartic acid (RGD) motif in the penton base of Ads to target cells integrin, specifically αvß3 [ 44 ].…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
“…They can elicit strong immune effects and are generally used in oncolytic therapy. 3 Lentiviral vectors are single-stranded RNA viruses that can efficiently accommodate 10 kb of a transgene. 4 They integrate their genetic material into the host genome, allowing long-term expression of the therapeutic gene.…”
Section: Treatment Effectmentioning
confidence: 99%
“…The use of dendritic cells, an important platform for T cell activation, as vaccines has also demonstrated interesting results in several studies Table 3. [68][69][70][71][72][73][74] Some other teams focused on the use of oncolytic viruses 75 with results to be demonstrated in clinical trials in the future. Cold-inducible RNA binding protein 73 or Tumor RNA-Loaded Lipid Nanoparticles 74 have also recently been study and demonstrated potential, especially in use with ICI.…”
Section: Dovepress 1041mentioning
confidence: 99%